Peran Pemerintah Desa dalam Peningkatan Kesejahteraan Masyarakat Desa Perdamean Kecamatan Tanjung Morawa Kabupaten Deli Serdang - Agatha Sofia Margareta; Rahma Dhani Fitria Sinaga; Nelly Moria Hutapea; Julia Ivanna (Indo-Fintech Intellectuals: Journal of Economics and Business, 2024)
The purpose of this research is to determine the implementation of Village government programs in efforts to improve community welfare in Perdamean Village, Tanjung Morawa District, Deli Serdang Regency, and to determine the inhibiting factors of Village government programs in efforts to improve community welfare in Perdamean Village, Tanjung Morawa District, Deli Serdang Regency. This research uses field research. The data sources used are primary data sources and secondary data sources from the Perdamean Village Office. Data were analyzed using qualitative descriptive methods. The community's enthusiasm is very high in taking part in this Empowerment Training with the aim of improving their lives. Increasing people's welfare from the economic sector, namely income, has experienced good changes